2020
DOI: 10.3389/fonc.2020.00387
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cerebrospinal Fluid MicroRNAs Associated With Leptomeningeal Metastasis From Lung Adenocarcinoma

Abstract: Background: Leptomeningeal metastasis (LM) has frequently been observed in patients with lung adenocarcinoma. So far, its diagnosis and disease course monitoring are still extremely difficult. Moreover, there is no effective treatment regimen for LM due to a lack knowledge on the molecular mechanism of LM. This study aimed to identify LM-related cerebrospinal fluid (CSF) miRNAs, which have potential value for diagnosing and monitoring LM and exploring the molecular mechanism. Methods: CSF miRNAs were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Moreover, miRNAs are more stable than mRNAs, and thus less prone to external contamination during sample processing, especially in body fluid tests, which showed great prognostic potential in clinical practice. Pan et al[ 26 ] revealed that miR-7641, as a cerebrospinal fluid miRNA, has potential value for diagnosing and monitoring leptomeningeal metastasis. These characteristics make them excellent candidates as circulating biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs are more stable than mRNAs, and thus less prone to external contamination during sample processing, especially in body fluid tests, which showed great prognostic potential in clinical practice. Pan et al[ 26 ] revealed that miR-7641, as a cerebrospinal fluid miRNA, has potential value for diagnosing and monitoring leptomeningeal metastasis. These characteristics make them excellent candidates as circulating biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Others have applied rare cell capture technologies to standard CSF cytology approaches to improve the detection sensitivity of tumor cells [ 56 , 57 , 58 , 59 ]. Approaches examining the genome, transcriptome, proteome, or miRNAs found in CSF may also hold future promise in diagnosing LM [ 37 , 60 , 61 , 62 ]. While these liquid biopsy technologies from CSF are promising in their potential to improve the diagnosis of LM, they have not yet been adopted in diagnostic guidelines or achieved widespread implementation in clinical practice.…”
Section: Diagnosis Of Lmmentioning
confidence: 99%
“…Half of the reported brain miRNAs were found in CSF exosomal fractions, and some miRNAs specifically expressed in brain tissues were detected in CSF but not in serum. Some clinical studies with a lack of controlled comparisons with serum miRNAs reported that cancer progression was associated with levels of certain onco-miRNAs in BM and LM samples [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that relatively low concentrations and small numbers of detectable extracellular miRNAs could be isolated from the CSF [ 19 , 20 , 21 ]. Other studies reported that CSF extracellular miRNAs are differently expressed in CNS diseases [ 22 , 23 , 24 ]. However, it is hard to confirm certain extracellular miRNAs in CSF as biomarkers for LM, and to correlate miRNA profiles with supportive multi-omics data such as CSF proteomics.…”
Section: Introductionmentioning
confidence: 99%